2018
DOI: 10.24036/wra.v6i1.101939
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rotasi Audit, Spesialisasi Industri KAP, dan Client Importance Terhadap Kualitas Audit (Studi dengan Pendekatan Earning Surprise Benchmark)

Abstract: This research was aimed to examine empirically the effect of several factors to audit quality. These factors are Audit Rotation, Audit Firm Specialization and Client Importance. The population that will be used in this research are company listed in Indonesia Stock Exchange. This study uses sampel of 85 manufacturing companies listed in Indonesia Stock Exchange in the period 2015-2017. In this study, audit quality is measured by earning surprise benchmark. The method used was purposive sampling. The method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 8 publications
3
11
0
2
Order By: Relevance
“…Research conducted by [19], [20] and [7] show that PAF industry specialization affects audit quality positively. Companies handled with professional auditors tend to be announced weaknesses in internal control [21].…”
Section: Connections Between Public Accounting Firm Industry (Paf) Specialization With Audit Qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…Research conducted by [19], [20] and [7] show that PAF industry specialization affects audit quality positively. Companies handled with professional auditors tend to be announced weaknesses in internal control [21].…”
Section: Connections Between Public Accounting Firm Industry (Paf) Specialization With Audit Qualitymentioning
confidence: 97%
“…The reputation of a public accounting firm will always be related to the firm's size, and the PAF reputation will be reflected on the auditors who perform professionally and independently without depending on clients [22]. A public accounting firm with a large capacity occasionally provides good audit results and suits the company's condition [7], [23].…”
Section: Connections Between Reputation Of Public Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current research, earnings surprise benchmark is the proxy of audit quality, to detect and uncover profit management committed by management for the purpose of avoiding reporting losses. According to Suciana and Setiawan (2018), audit quality is categorized into two: 1. Audit quality is high (MEET_BE=1) if the profit value falls in the range of normal value.…”
Section: Dependent Variablementioning
confidence: 99%
“…Numerous studies in Indonesia have examined audit quality, but very few have been found to use earnings surprise benchmark -a proxy employed to assess audit quality which emphasizes on profit quality (Suciana & Setiawan, 2018). Herianti and Suryani (2016) conducted a study regarding audit quality by modifying measurements that had been adjusted to the conditions in Indonesia.…”
Section: Introductionmentioning
confidence: 99%